Stiftung Günther und Carola Peill Köln 1976. - Stiftung Günther und Carola Peill, Köln; Wallraf-Richartz-Museum, Köln; Museum Ludwig, Köln (Köln : Städt Köln, 1976)
Baumeister, Willi ; Beckmann, Max ; Corneille ; Ernst, Max ; Feininger, Lyonel ; Giacometti, Alberto ; Gilles, Werner ; Hartung, Hans ; Henri, Florence ; Jawlensky, Alexej ; Jorn, Asger ; Kandinsky, Wassily ; Kassák, Lajos ; Kerkovius, Ida ; Kirchner, Ernst Ludwig ; Klee, Paul ; etc.
Stiftung Günther und Carola Peill Köln 1976, Ausstellung der Stiftung und Sammlung Günther und Carola Peill, 12. Mai 1976 bis 25. JUli 1976, Wallraf-Richartz-Museum, Köln ; Museum Ludwig, Köln
boek